2020
DOI: 10.1093/ecco-jcc/jjaa016
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylation by MS-275 Alleviates Colitis by Activating the Vitamin D Receptor

Abstract: Background Ulcerative colitis [UC] is a common chronic inflammatory bowel disease without curative treatment. Methods We conducted gene set enrichment analysis to explore potential therapeutic agents for UC. Human colon tissue samples were collected to test H3 acetylation in UC. Both in vivo and in vitro colitis models were constructed to verify the role and mechanism of H3 acetylation modification in UC. Intestine-specific v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…As reported, gut epithelial VDR inhibited colitis by protecting the mucosal epithelial barrier and maintaining mucosal integrity (19,27), although only a few studies illustrated the mechanism of this protective effect against colitis. Here, we found that VDR knockout in the intestinal epithelium suppressed mucosal absorptive function in vivo (Fig.…”
Section: J O U R N a L P R E -P R O O F Vdr Deficiency Impaired Epithmentioning
confidence: 87%
See 3 more Smart Citations
“…As reported, gut epithelial VDR inhibited colitis by protecting the mucosal epithelial barrier and maintaining mucosal integrity (19,27), although only a few studies illustrated the mechanism of this protective effect against colitis. Here, we found that VDR knockout in the intestinal epithelium suppressed mucosal absorptive function in vivo (Fig.…”
Section: J O U R N a L P R E -P R O O F Vdr Deficiency Impaired Epithmentioning
confidence: 87%
“…In addition, VDR had an inhibitory effect on the phosphorylation of Smad2/3, which is a classic downstream molecule of TGFβ1. To verify the effects of VDR on intestinal epithelia in EMT-related fibrosis, we established intestinal fibrosis models with intestinal epithelial-specific VDR-knockout mice (20) and littermate controls. Mice with epithelial VDR deficiency developed worsened intestinal fibrosis in both the chronic TNBS and DSS models, followed by exacerbated EMT and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lysine acetylation is a common posttranslational modification (PTM) regulating protein stability, subcellular localization, and function [17]. Acetylation of histone and nonhistone was reported to be involved in many diseases, including aging-associated chronic inflammation and insulin resistance [18], cancer [19][20][21], colitis [22], and Alzheimer's disease [23]. In previous work, we analyzed the lysine acetylproteome in three primary cervical cancer tissues and corresponding adjacent normal tissues by using the label-free proteomics approach and found that acetylation levels of CLIC1 at lysine 131 were significantly increased in tumor tissues.…”
Section: Introductionmentioning
confidence: 99%